1998
DOI: 10.1084/jem.187.6.885
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Studies of the Primary Immune Response to (4-Hydroxy-3-Nitrophenyl)Acetyl. V. Affinity Maturation Develops in Two Stages of Clonal Selection

Abstract: To examine the role of germinal centers (GCs) in the generation and selection of high affinity antibody-forming cells (AFCs), we have analyzed the average affinity of (4-hydroxy-3-nitrophenyl)acetyl (NP)-specific AFCs and serum antibodies both during and after the GC phase of the immune response. In addition, the genetics of NP-binding AFCs were followed to monitor the generation and selection of high affinity AFCs at the clonal level. NP-binding AFCs gradually accumulate in bone marrow (BM) after immunization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
325
1
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(358 citation statements)
references
References 59 publications
31
325
1
1
Order By: Relevance
“…The memory B cell response to the T-dependent Ag NP-CGG develops via a GC-dependent process culminating in the formation of Ag-experienced memory B cells and PCs (31,39). Classswitched NIP + IgG1 + GC B cells were present in normal numbers from days 14-35 in NP-CGG-immunized IL-21R.KO mice, further highlighting that signals delivered via IL-21R are not required for GC maintenance.…”
Section: Discussionmentioning
confidence: 71%
“…The memory B cell response to the T-dependent Ag NP-CGG develops via a GC-dependent process culminating in the formation of Ag-experienced memory B cells and PCs (31,39). Classswitched NIP + IgG1 + GC B cells were present in normal numbers from days 14-35 in NP-CGG-immunized IL-21R.KO mice, further highlighting that signals delivered via IL-21R are not required for GC maintenance.…”
Section: Discussionmentioning
confidence: 71%
“…Recently, it has been shown that the inappropriate distribution of B cells outside the GC may result in the loss of censoring the development of autoreactive B lymphocytes (50). Work by Kelsoe and coworkers (51) have shown that affinity selection can occur outside the GC. Whereas it is clear that the BM plays a critical role in positive and negative selection during B cell ontogeny, the question emerges as to whether the BM also plays a role in the censorship of affinity-matured B cells before terminal differentiation to PCs.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of B cells presenting antigen with primed T cells occurs in the outer T zone and the adjacent regions of the B cell follicles [24,25]. Activated B cells either migrate to follicles, where they form germinal centers and undergo affinity maturation [30], or to medullary cords where they differentiate to plasmablasts and then plasma cells. The medullary cord plasmablasts to not undergo Ig V-region gene mutation [24,28].…”
Section: Isolation Of the Differentiating B Cell Subsets During Lymphmentioning
confidence: 99%